Cost of acute coronary syndrome in Switzerland in 2008 (Swiss Medical Weekly, 2012)
QUESTIONS UNDER STUDY: To perform a cost-of-illness study of acute coronary syndrome (ACS) in Switzerland from a societal perspective, evaluating direct costs, production losses and intangible costs in terms of quality adjusted life years (QALYs) lost. METHODS: A bottom-up incidence-based approach was used. Data concerning patients with one or more ACS events were extracted from a national hospital database and from mortality statistics. Inpatient costs included acute care and rehabilitation. Outpatient costs included costs for ambulance, visits to GP and cardiologist, outpatient diagnostics, medication and rehabilitation. Production losses included absenteeism, permanent disability and premature death. Intangible costs were calculated on previously published QALY weights. Cost data were derived from official price lists, literature and experts. Future costs and QALYs lost were discounted. RESULTS: In 2008 14,955 patients experienced a total of 16,815 ACS events; 2,752 died as a consequence of these. The resulting 19,064 hospital stays had an average across-hospital length of stay of 9.1 days per patient. Total direct costs of ACS amounted to 630 Mio Swiss Francs (CHF) for society and CHF 462 Mio for health insurers. Total direct costs were dominated by costs of myocardial infarction: ST-elevation 45.8%, non-ST-elevation 35.8%. Production losses were CHF 519 Mio and intangible costs resulted in 49,878 QALYs lost. CONCLUSIONS: ACS causes considerable costs in terms of direct medical expenditures, lost production, suffering and premature death, even without taking into account costs for its chronic consequences such as congestive heart failure.